Characterization of Phospholipase A2 Enzyme Activity in Serum of the Komodo Dragon (Varanus Komodoensis) - Merchant, Mark; Muscher, Bekky; Bryja, Judith; Henry, Danyell; Falconi, Rodolfo (JOURNAL OF ADVANCES IN BIOLOGY, 2018)
Soluble phospholipase A2 (sPLA2) is an enzyme found in the peripheral circulation of vertebrates which has significant immunological activity. This enzyme exerts immune activity by the hydrolysis of fatty acids from the sn-2 position of membrane glycerophospholipids of microbes, thus compromising membrane integrity and casing eventual lysis. We utilized membrane fatty acids labeled with a fluorescent probe (BODIPY) at the sn-2 position fatty acid to label the membranes. Incubation of different volumes of serum from Komodo dragons with BODIPY-labeled bacteria resulted in liberation of labeled fatty acid in a serum volume-dependent manner. This cleavage of fatty acid occurred rapidly, with a biphasic production of fluorescent product. An immediate accumulation of product was noted, which increased steadily for a 30-minute period, followed by a slower hydrolysis between 30 and 180 min. The activity was temperature-dependent, with low activities observed at 5oC and a linear increase up to 40oC. The liberation for fatty acid was inhibited by p-bromophenacyl bromide, a specific phospholipase A2 (PLA2) inhibitor, in a concentration-dependent manner, indicating that the activity was due to the presence of sPLA2.